Cultural differences between university students in online learning quality and psychological profile during COVID-19 - Simone Nomie Sato; Emilia Condes Moreno; Adriana Rico Villanueva; Paulo Orquera Miranda; Pascual Chiarella; Jose Francisco Tornero-Aguilera; Vicente Javier Clemente-Suárez (Journal of Risk and Financial Management, 2022)
During the COVID-19 pandemic, educational systems had to adapt to the social and health situation immediately. This led to the appearance of the asynchronous teaching model. Throughout the pandemic at an educational level, we can distinguish three phases, eminently online, hybrid, and face-to-face. However, the perception of educational quality in these three educational moments, considering the psychometric profile and cultural differences comparing Ibero-American countries, has not been studied. The study aims to analyze the psychological profile, and perception of quality in the teaching-learning processes at the university stage, during the three processes of educational transition during COVID-19: online, hybrid, and face-to-face. Thus, 1093 university students from Ibero-American countries were studied. Through a questionnaire, demographic, academic, and psychological variables were analyzed during three phases of the pandemic. Data suggest that Latin American students had higher levels of trait anxiety and stress perception, as well as higher levels of loneliness, during the online teaching phase (lockdown), but higher grades and higher levels of motivation compared to Europeans. Indeed, Latin Americans showed greater convenience, and preference for online learning methods. However, during the face-to-face teaching phase, European students presented greater motivation and grades, showing a greater preference for this method of learning than Latin American students. Factors such as resilience, a more unfavorable and pronounced pandemic evolution, and greater social inequities, may explain the present results. Furthermore, the present study suggests that despite the effect of the pandemic on mental health, online education is postulated as an effective teaching-learning alternative. Indeed, online teaching models have come to stay, not as a substitute, but as a tool, an essential focus of attention on these models should be conducted in European countries, while the governments of Latin American countries ensure that the infrastructures and resources are equitable to be able to correctly implement this teaching model.
Keywords: 650; COVID-19; mental health; gender differences; hybrid education; online teaching